Experimental Study on the Factors Influencing the Thermal Performance of Vaccine Refrigeration Vehicles - Zhao Juan; Zhang Zhongbin; Chen Meng; Gan Qiang; Gong Li; Song Ping; Deng Qingqing (Zhileng xuebao)
To investigate the temperature distribution and optimize the thermal performance of a vehicle carriage for transporting refrigerated vaccines, a 3.9 m3 vehicle carriage working within the temperature range of 2–8 °C is examined in this study. Four factors, namely, solar radiation intensity, air duct structure, refrigeration unit switch, and door curtain, which influence the thermal performance, are experimentally studied at a compressor speed of 1 800 r/min. The uniformity of the temperature distribution and the temperature change rate during the measurement period are comprehensively analyzed. The results show that when the vaccine refrigeration vehicle is maintained under an average solar radiation intensity of 295.94 W/m2and 82.78 W/m2 for two hours, the average temperature in the carriage under the former condition is 1.326 °C higher than that under the latter. The on-off frequencies of the refrigeration units increase, and the energy consumption of the vehicle increases. The application of the air duct structure can help reduce the local hot spots in the carriage, and the rate of pre-cooling increases by 0.006 °C/s. Moreover, when the carriage door is opened for 120 s, continuous operation of the refrigeration unit enhances the airflow heat exchange between the inside and outside of the carriage, which noticeably disturbs the temperature distribution in the vehicle. Therefore, closing the refrigerating unit is recommended when the vehicle door is opened. The curtain can effectively prevent cold air from exchanging heat with the environment and maintain the low temperature of the carriage.